Raineya orbicola gen. nov., sp. nov. a slightly thermophilic bacterium of the phylum bacteroidetes and the description of raineyaceae fam. nov - Albuquerque L. (2018)
An isolate, designated SPSPC-11T, with an optimum growth temperature of about 50°C and an optimum pH for growth between 7.5 and 8.0, was recovered from a hot spring in central Portugal. Based on phylogenetic analysis of its 16S rRNA sequence, the new organism is most closely related to the species of the genus Thermonema but with a pairwise sequence similarity of <85 %. The isolate was orange-pigmented, formed non-motile long filaments and rod-shaped cells that stain Gram-negative. The organism was strictly aerobic, oxidase-positive and catalase-positive. The major fatty acids were iso- C15:0, iso-C15: 0 2-OH and iso-C17: 0 3-OH. The major polar lipids were one aminophospholipid, two aminolipids and three unidentified lipids. Menaquinone 7 was the major respiratory quinone. The DNA G+C content of strain SPSPC-11T was 37.6 mol% (draft genome sequence). The high quality draft genome sequence corroborated many of the phenotypic characteristics of strain SPSPC-11T. Based on genotypic, phylogenetic, physiological and biochemical characterization we describe a new species of a novel genus represented by strain SPSPC-11T (=CECT 9012T=LMG 29233T) for which we propose the name Raineya orbicola gen. nov., sp. nov. We also describe the family Raineyaceae to accommodate this new genus and species. © 2018 IUMS.